2015
DOI: 10.1159/000381344
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multipeptide Microarray for the Specific and Sensitive Mapping of Linear IgE-Binding Epitopes of Food Allergens

Abstract: Background: The identification of B-cell epitopes of food allergens can possibly lead to novel diagnostic tools and therapeutic reagents for food allergy. We sought to develop a flexible, low-tech, cost-effective and reproducible multipeptide microarray for the research environment to enable large-scale screening of IgE epitopes of food allergens. Methods: Overlapping peptides (15-mer, 4 amino acid offset) covering the primary sequence of either peanut allergen Ara h 1 or all 3 subunits of the soybean allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…More recently, Kühne and colleagues compared peanut allergen Ara h 1 and the soybean allergen Gly m 5 using SPOT membrane technology and microarray slides . They found a 98% reproducibility between these techniques, although some additional IgE‐binding peptides were identified using microarray.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Kühne and colleagues compared peanut allergen Ara h 1 and the soybean allergen Gly m 5 using SPOT membrane technology and microarray slides . They found a 98% reproducibility between these techniques, although some additional IgE‐binding peptides were identified using microarray.…”
Section: Resultsmentioning
confidence: 99%
“…We found that only six studies addressed this question. Two studies analyzed technical sensitivity and specificity and concluded that microarray is a robust technology that can be applied for epitope mapping of food allergens with results that are comparable to previous SPOT membrane technique. Four studies analyzed the diagnostic sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…101 Celluspot™ peptides (15 amino acids, 4 amino acids offset) covering the entire primary structure of Pis s 1.0101 (Uniprot number Q702P1) were synthesized, as previously described, 29 on cellulose support, and spotted in quadruplicate onto microscope slides (Intavis AG). DMSO solvent was multiply spotted as a control for background signal.…”
Section: Generation and Immunodetection Of Pis S 1 Multipeptide Micmentioning
confidence: 99%
“…Indoor Biotechnology produces an IgE quantitative binding array for the simultaneous detection and quantitative determination of total and allergen-specific human IgE against 11 allergens. Kühne et al [47 ]demonstrated, in a proof-of-concept study, that multipeptide microarrays of the peanut allergen Ara h 1 and all 3 subunits of the soybean allergen Gly m 5 could be used for large-scale screening of IgE epitopes of food allergens.…”
Section: Recombinant Allergens In Diagnostic Testsmentioning
confidence: 99%